Elucidation of the structure and function of the Mycosins, a family of essential subtilisin-like serine proteases of Mycobacterium tuberculosis - Fang, Zhuo (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.